البصمة الوراثية وتقدير التباينات الوراثية في مدخلات البازلاء باستخدام مؤشرات الـ AFLP (مجلة جامعة اللاذقية- سلسلة العلوم البيولوجية, 2018)
In order to identify efficient strategies for the sustainable management of the genetic resources of the landraces, we have investigated in this study the level of genetic diversity in 81 accessions of Pisum belonging to the two species P. sativum and P. fulvum. The  accessions had 6 different origins. DNA was extracted and analyzed by amplified fragment length polymorphism (AFLP) technique. Seven primer combinations were used to produce DNA fingerprints for the 81 accessions. 289 polymorphic fragments were identified. The number of polymorphic fragments in the different accessions varied from 46 to 225, and the percentage of polymorphic fragments ranged between 18.93% and 92.59%. A specific DNA  pattern for each accession was identified. Based on the data of AFLP, we estimated the genetic distance between the different accessions. The level of genetic diversity detected within species was higher than the one detected between species. The utility of the molecular markers in the development of collection strategies  is  also discussed in this paper. تم في هذه الدراسة تقدير مستوى التنوع الوراثي لأحد وثمانين مدخلاً من الجنس Pisum ينتمون للنوعين P. sativum و P. fulvum باستخدام مؤشرات AFLP وذلك بهدف تحديد الية مناسبة للادارة المستدامة للأصول الوراثية. تم جمع العينات من ستة أماكن مختلفة. استخدمت سبعة أزواج من بادئات الـ AFLP  في تحليل DNAالمدخلات. أظهرت النتائج وجود 289 قطعة مختلفة من الـ DNA، وقد تباين عدد هذه القطع ما بين المدخلات  المختلفة حيث تراوح عددها ما بين 46 و 225 قطعة، وهذا يقابل نسبة تباينات تتراوح ما بين 39و18% و59و92%. تم تحديد  بصمة وراثية خاصة بكل مدخل ومن ثم تم حساب البعد الوراثي بين المدخلات اعتماداً على معطيات تقنية الـ AFLP، و أنشئت المخططات التي تعكس الاختلافات بين أنواع  Pisum المختلفة. أظهرت النتائج بان مستوى التباين الوراثي ضمن النوع الواحد هو أكبر من ذلك الموجود بين النوعين. تمت، في نهاية البحث، مناقشة إمكانية الاستفادة من المؤشرات الجزيئية في تطوير طرق والية لجمع العينات النباتية لحفظ الأصول الوراثية للبازلاء. تم تنفيذ البحث في المركز الدولي للبحوث الزراعية في المناطق الجافة(ايكاردا)، حلب، سوريا عام 2005.